Pelatihan Pengembangan Media Pembelajaran Interaktif Berbasis Teknologi bagi Guru di Sekolah SMP Muhammadiyah 07 Sukaraja - Syaiful Anam; Muhamad Nanang Rifa'i; Ajeng Nazah Fauziah (CV. Denasya Smart Publisher, 2025)
This Community Service (PkM) activity aims to improve teacher competency in developing technology-based interactive learning media at Muhammadiyah 07 Sukaraja Junior High School. In today's digital era, the use of innovative and interactive learning media is key to creating an engaging, effective, and digitally-adapted teaching and learning process. Through participatory training, teachers were provided with an understanding of the importance of interactive media, introduced to various educational applications and platforms, and directly guided in creating technology-based learning media. The results of the activity demonstrated improved teacher skills and enthusiasm in designing interactive media. This activity is expected to have a sustainable impact on improving the quality of education at Muhammadiyah 07 Sukaraja Junior High School.